The Relevance of Tetravalent Influenza Vaccines. World experience - A. D. M. E. Osterhaus (Эпидемиология и вакцинопрофилактика)
An overview of influenza virology, epidemiology and evolution history peculiarities is given. Data from international influenza survey and own study results are presented demonstrating influenza virus high pandemic potency due to its ability to change constantly. Using the examples of seasonal influenza minor but constant changes, virtual pandemic hazard is discussed. Based on the international surveillance data and using mathematical model findings, vaccination is considered to be most effective preventive measure, and justification for quadrivalent influenza vaccine apply, especially in young persons is presented.